2022
DOI: 10.1038/s41390-021-01884-x
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic supplementation in neonates with congenital gastrointestinal surgical conditions: a pilot randomised controlled trial

Abstract: Objective To evaluate whether probiotic supplementation attenuates gut-dysbiosis in neonates with congenital gastrointestinal surgical conditions (CGISC). Methods Sixty-one neonates (≥35 weeks gestation) with CGISC were randomised to receive daily supplementation with a triple-strain bifidobacterial probiotic ( n = 30) or placebo ( n = 31) until discharge. Stool microbiota was analysed using 16S ribosomal RNA gene se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 60 publications
0
19
0
Order By: Relevance
“…Probiotic supplementation has become increasingly popular in the fight against gut microbiota depletion. 16,20,21 A randomized control trial was conducted by Zhong et al to assess the impact of probiotic supplements on 90 neonates with gestational age ≥ 37 weeks. The study concluded that antibiotics cause a decrease in the microbial richness and variety of the gut microbiota in neonates and the attenuation of several bacteria, especially Bifidobacterium and Lactobacillus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Probiotic supplementation has become increasingly popular in the fight against gut microbiota depletion. 16,20,21 A randomized control trial was conducted by Zhong et al to assess the impact of probiotic supplements on 90 neonates with gestational age ≥ 37 weeks. The study concluded that antibiotics cause a decrease in the microbial richness and variety of the gut microbiota in neonates and the attenuation of several bacteria, especially Bifidobacterium and Lactobacillus.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 A relative reduction in the Bifidobacteriaceae counts and an increase in Enterobacteriaceae and Clostridiaceae may be a good criterion to define dysbiosis in the initial months of life. 11,16 It can also explain gut colonization between birth, which can serve as the basis for introducing nutritional strategies targeted at the microbiota. These nutritional interventions, based mainly on probiotics, may be used for favourably altering the gut microbiome and preventing neonatal sepsis.…”
Section: Introductionmentioning
confidence: 99%
“…Our pilot RCT found that the head circumference growth was better in the probiotic group. 1 Hence, one could hypothesise that the probiotic supplemented group will have better neurodevelopmental outcomes. Our retrospective study 5 with a sample size of 400 found the incidence of suboptimal neurodevelopmental outcomes to be 16% in term and near-term infants with CGISC.…”
Section: Sample Sizementioning
confidence: 99%
“…Our pilot randomised controlled trial (RCT) 1 found that supplementation with the three-strain probiotic containing Bifidobacterium breve M-16V, Bifidobacterium longum subsp. infantis M-63 and Bifidobacterium longum subsp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation